PAX5 ALTERATIONS IN CHILDREN, ADOLESCENTS AND YOUNG ADULTS WITH B-OTHER ACUTE LYMPHOBLASTIC LEUKEMIA - TFD Amaral; MD Villares; CB Blunk; BA Lopes; TC Barbosa; M Emerenciano (Hematology, Transfusion and Cell Therapy)
B-cell precursor acute lymphoblastic leukemia (B-ALL) is the most prevalent form of ALL and its development varies with age. It is characterized by chromosomal and genetic alterations such as aneuploidy, gene fusions, copy number alterations (CNA) and point mutations, which are crucial for diagnosis and therapy risk stratification. However, ̃25% of pediatric and ̃8% of adult cases with B-ALL lacking recurrent alterations are classified as “B-other”. New clinically relevant genetic alterations involving PAX5 gene are being demonstrated in this subtype, including rearrangements (PAX5 -r), deletions (PAX5 del), amplifications (PAX5 amp), and a point mutation (PAX5 P80R). Around 30% of B-ALL cases show PAX5 alterations (PAX5 alt), which are associated with relapses and poor outcomes. This study aims to characterize PAX5 alterations and evaluate their prognostic impact in children, adolescents and young adults (AYA) with B-other ALL. Pediatric (< 15 years) and AYA (15-39 years) cases diagnosed with B-ALL between 2018 and 2023 in different Brazilian cancer treatment centers were included. Recurrent and primary alterations were previously characterized by reverse transcription PCR (RT-PCR) or quantitative PCR (qPCR). Only patients categorized as B-other, defined by the lack of ETV6::RUNX1, BCR::ABL1, TCF3::PBX1, KMT2A::AFF1 and high-hyperdiploidy (DNA index), were included. CNA were identified by multiplex ligation-dependent probe amplification (MLPA), using the P335-C1 probemix (MRC-Holland). PAX5 -r were detected by fluorescence in situ hybridization (FISH - ZytoLight SPEC PAX5 Dual Color Break Apart Probe - Zyto Vision), and the PAX5 P80R mutation was assessed by TaqMan customized allelic discrimination assay (Life Technologies). This study was approved by the institutional ethical committee (CAEE #87793418.0.0000.5274). A total of 62 B-other ALL cases were evaluated (44 pediatric and 18 AYAs). Approximately 27% of these cases were characterized as PAX5 alt, due to the presence of PAX5 amp (̃23%), PAX5 del (̃52%) or PAX5 -r (̃41%), occurring alone or simultaneously. In this subtype, most cases were pediatric (71%), with a median age of 8 years-old, and low white blood cell count at diagnosis (̃64%). CDKN2A/B del (̃47%) and JAK2 del (̃17%) were concomitantly observed with PAX5alt. On the other hand, in PAX5 wild-type patients, CDKN2A/Bdel (̃26%) and IKZF1 del (20%) were the most prevalent. Curiously, the IGH -rearrangements were commonly found among PAX5 alt cases (̃23%). PAX5 P80R were not found in any cases. Considering that the genetic alterations knowledge is essential for the treatment decisions, a better understanding of PAX5 alterations in B-other ALL is crucial for precision medicine. Besides, our findings suggest that the IGH gene may be a frequent partner of PAX5 fusions, though it requires further investigation.